Great world religions Christianity - Johnson, Luke Timothy (Chantilly, Va. Teaching Co., 2003)
Consists of twelve 30-min. lectures that provide an overview of Christianity. Explains why the central figures, elements, and creeds of Christianity give Christianity its distinctive character. Covers Christianity's birth and expansion across the Mediterranean world, the development of its doctrine, its assertion that Jesus was both a man and God, its transformation upon becoming Rome's imperial religion, its many and deep connections to Western culture, and the tensions in Christianity today.
disc 1. Christianity among world religions. Birth and expansion. Second century and self-definition. Christian story. What Christians believe. Church and sacraments -- disc 2. Moral teaching. Radical edge. Catholic, Orthodox, Protestant. Christianity and politics. Christianity and culture. Tensions and possibilities.
"Library edition"--Container.
"Course Number 6101."
DVD, region 1.
Keywords: Catholic Church; Orthodox Eastern Church; Christianity; Protestantism; Church history -- Early church, ca. 30-600.; Philosophy and religion